THE CORRELATIVE STRATEGIES TO THE STRENGTH OF MON'S COMMUNITY IN PATHUMTHANI PROVINCE - บุญญาสถิต, วรรณพร; ศิริวรสกุล, วณิฎา; อินทพรหม, วัชรินทร์ (Academic Journal Phranakhon Rajabhat University, 2018)
The objectives of this research are: 1) to explore traditional customs and arts of Mon, 2)to study the relationship between Mon’s customs and culture and their stratagem attributing Mon’s consolidation, and 3) to propose Mon’s culture dissemination strategy with the stratagem attributing consolidation for Mon’s community in Prathumthani Province. This research applies a mix of qualitative and quantitative methods. Interview is used as a research tool to gather data. Key informants include 36 community leaders and officials involved with Mon’s culture conservation. In addition, questionnaires are given to collect data, and the samples are 372 families of Mon people in 6 communities in Pratumthani province. Descriptive statistic used are frequency, percentage, means, and standard deviation. The results revealed that: 1) Songkhaowchae Festival is the Mon’s traditional custom attributing harmonious and consolidating their community, 2) There are 6 factors contributing Mon’s community consolidation which include (1) Social wise, Mon’s social relationship is described as relative community, rated in high average score. (3) In term of social organizations, collaborated goals are determined. (4) Culture and traditional custom wise, identically they have strong and outstanding cultures. (5) Learning wise, there is a inheriting of culture knowledge.(6) Economic wise, they practice sufficient economic philosophy. 3) The correlation of Mon’s culture and traditional custom in which contributing their social consolidation are comprised of many traditional customs which are Songkhaowchae, Hea-No, Buddhist bathing, Loi Kao, Tamboon Peekrajad, Mixed food offering during Buddhist Lent, 10th Lunar month merit making, Kaowthip cooking, Honey offering, Klangbaan merit making, rice dance, hundred monks food offering, ancestry spirit worshiping, village spirit house ceremony, Looknoo lighting, No-nea song, Mon dance, Sabaa Mon playing, Sabaatoy playing Peekadong playing, Kaopeeling and Kaopeesuem playing, paper perforating for coffin, and Mon’s Chedi constructing. These traditional customs significantly relate to Mon’s social consolidation, with the statistical significance of 0.00 (α=0.05). 4) Mon’s culture conservation and dissemination strategies with the stratagem attributing consolidation for Mon’s community in Prathumthani Province include (1) art and culture restoring, (2) art and culture conservation, (3) dissemination of art and culture, and (4) inheriting of art and culture.